RURAL POVERTY AND ITS IMPACT IN SHEN CONGWEN’S SHORT STORY THE HUSBAND - Wahyuningsih, Ekawati Tyas; Wuryandari, Nurni Wahyu (International Review of Humanities Studies, 2021)
Shen Congwen (1902-1988) is a modern Chinese author and poet who is known for his native-soil literature (xiangtu wenxue). The short story The Husband (Zhangfu, 1930) is one of his works in native-soil literature. It tells a story about the character “Husband” who lived as a peasant in the barren and poor Huang Village. Like other husbands in the village, he sent his wife to work in the city to improve the family finances. At the end of the story, the character “Husband” decided to take his wife home to the village after he witnessed firsthand the life in the city and how his wife worked. This study examines how Shen Congwen discussed rural poverty and its impact on Huang Village. This study uses an intrinsic approach that focuses on the description of the social situation and the characterization presented by Shen in the short story. It is then strengthened with the description of the social condition happening in China outside of the literary works. The study finds that the main problem that caused the husbands to send their wives to work in the city is poverty and their desire to improve family finances. The root cause of the poverty is the barren village land and the tax to be paid by the villagers for the upper class. Shen sympathized with the villagers by telling the story of “Husband” and the events happening in the short story to reveal the disarray in 1930’s China.